Application of sludge, organic solid wastes and yard trimmings in aerobic compost piles - Chazirakis, P. (2016)
The effects of different mixture ratios of sewage sludge (SS), organic fraction of municipal solid waste (OFMSW) and yard trimmings (YT) on the performance of composting process were investigated in this study. The high water content and the proper carbon/nitrogen ratio make sludge ideal for this procedure, improving the characteristics of the initial composting mixture. OFMSW and YT enable the production of a quality product that may be used as a soil conditioner. Therefore, piles of about 1 m3 were prepared by mixing OFMSW, SS and YT in four different ratios (w/w) [only OFMSW, OFMSW:SS = 2:1, OFMSW:SS:YT = 3:1:2, and OFMSW:SS:YT = 4:1:2]. The piles were kept in controlled aerobic conditions for 10 weeks. The temperature of the piles was measured daily (for the first 4 weeks) and ranged between 60-70 oC, while air was provided to the piles by mechanical turning. Results showed that the pile OFMSW:SS:GW = 3:1:2 was most beneficial in composting, since its ability to accumulate and retain heat and achieve high organic matter degradation. The final compost products contained C/N ratio less than 15 indicating that achieved mature and stable products. The heavy metal contents in the final composts were several times lower than regulation limits.